2021
DOI: 10.1108/jiabr-04-2021-0115
|View full text |Cite
|
Sign up to set email alerts
|

Economics of savings-based finance: an interest-free model of rotating savings and credit association in Turkey

Abstract: Purpose The emerging markets have been witnessing a remarkable revival of rotating savings and credit associations (ROSCAs) serving as alternative informal financing and investment platforms, also known as savings-based finance (SBF) in Turkey. The purpose of this study is to present the SBF model mathematically, analyse the performance of the SBF sector and propose a new Sharīʿah-compliant SBF model for the acquisition of durables. Design/methodology/approach The paper thoroughly reviews the concept and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Hence, this activity became a solution to solve the community's financial problem. This is consistent with the findings of Dinç et al (2022). Similarly, Rabie's (2021) findings in Africa suggested that ROSCA plays an important role as a tool for saving and investing when economic sistuation is moderate and low.…”
Section: The Practice Of Jula-jula In North Sumatrasupporting
confidence: 86%
See 1 more Smart Citation
“…Hence, this activity became a solution to solve the community's financial problem. This is consistent with the findings of Dinç et al (2022). Similarly, Rabie's (2021) findings in Africa suggested that ROSCA plays an important role as a tool for saving and investing when economic sistuation is moderate and low.…”
Section: The Practice Of Jula-jula In North Sumatrasupporting
confidence: 86%
“…Indeed, it has been discovered that the jula-jula practices of the Tapanuli Bataknese society contain characteristics of usury. It also incorporates an aspect of tyranny, which contradicts prior studies by Sadr (2017) and Yusuf (as cited in Dinç, Jahangir, Nagayev, & Çakır, 2022). Hence, it is essential that the current study investigates the implementation of jula-jula within the Tapanuli Muslim community from an Islamic economics perspective.…”
Section: Introductionmentioning
confidence: 81%
“…Furthermore, several other research were conducted by focusing on the economics of SBF or ROSCA (Aliber, 2001;Kedir, 2005;Dinç et al, 2021), interest-based and interest-free ROSCA model (Sadr, 2017;Le Polain et al, 2018;Ke and Ye, 2019), institutional aspect of ROSCA (Schirmeister and Nadler, 1996;Van den Brink and Chavas, 1997;Ibrahim, 2019), the practice of ROSCA (Ardener, 1964;Anderson, 1966;Adams and de Sahonero, 1989), the operational behaviour of ROSCA (Laguerre, 1998;Osei-Assibey, 2015), risk management (Baland et al, 2019;Han et al, 2020;Reito, 2020), and digitalization of ROSCA (Bouman, 1979;Abdul-Yakeen, 2012;Mehmood et al, 2019;Francois and Squires, 2021). Finally, there are some studies that primarily bolster the objective of this research, i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though there is no universally recognized definition or formation of ROSCA in literature, various scholars have defined it differently over time. For instance, Ardener (1964) defined the concept as: "[A]n association formed upon a core of participants who agree to make regular contributions to a fund which is Source(s): Authors [Dinç et al, (2021)] -20.00% 0.00% 20.00% 40.00% 60.00% 80.00% 1 9 5 1 1 9 9 1 1 9 9 2 2 0 1 6 2 0 1 7 2 0 1 8 2 0 1 9 2 0 2 0 Total Linear (Total) given, in whole or in part, to each contributor in rotation" (p. 201). Yu (2013) defined ROSCA as "financial self-help groups that collect multiple contributions from their members across time and allocate merged funds back generally in rotation" (p. 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation